2017
DOI: 10.1371/journal.pone.0183191
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the 13-valent pneumococcal conjugate vaccine in preventing invasive pneumococcal disease in children aged 7-59 months. A matched case-control study

Abstract: BackgroundThe 13-valent pneumococcal conjugate vaccine (PCV13) was licensed based on the results of immunogenicity studies and correlates of protection derived from randomized clinical trials of the 7-valent conjugate pneumococcal vaccine. We assessed the vaccination effectiveness (VE) of the PCV13 in preventing invasive pneumococcal disease (IPD) in children aged 7–59 months in a population with suboptimal vaccination coverage of 55%.MethodsThe study was carried out in children with IPD admitted to three hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 37 publications
6
53
0
Order By: Relevance
“…15 In contrast, PCV15-B showed significant improvement in vaccine performance for most serotypes in PCV15 in comparison to PCV15-A and the initial formulation evaluated in the study by Greenberg et al 15 Improved immune responses observed for PCV15-B were observed for both IgG GMCs and proportion of subjects achieving threshold value of ≥0.35 µg/mL at both PD3 and PD4. Study results from both studies also confirmed results from previous studies showing that both PCV15-A and PCV15-B induce higher antibodies than PCV13 to serotype 3 for which the effectiveness of the licensed PCV13 appears to be inconsistent, sometimes due the small size of the study cohort [28][29][30][31] ; however, the clinical significance of the observed difference in antibody levels between recipients of PCV15 and PCV13 is unknown without real world evidence of PCV15 effectiveness against disease caused by serotype 3. Moreover, both PCV15-A and PCV15-B induce higher antibody responses than PCV13 to the 2 serotypes unique to PCV15 (serotypes 22F and 33F).…”
Section: Discussionsupporting
confidence: 82%
“…15 In contrast, PCV15-B showed significant improvement in vaccine performance for most serotypes in PCV15 in comparison to PCV15-A and the initial formulation evaluated in the study by Greenberg et al 15 Improved immune responses observed for PCV15-B were observed for both IgG GMCs and proportion of subjects achieving threshold value of ≥0.35 µg/mL at both PD3 and PD4. Study results from both studies also confirmed results from previous studies showing that both PCV15-A and PCV15-B induce higher antibodies than PCV13 to serotype 3 for which the effectiveness of the licensed PCV13 appears to be inconsistent, sometimes due the small size of the study cohort [28][29][30][31] ; however, the clinical significance of the observed difference in antibody levels between recipients of PCV15 and PCV13 is unknown without real world evidence of PCV15 effectiveness against disease caused by serotype 3. Moreover, both PCV15-A and PCV15-B induce higher antibody responses than PCV13 to the 2 serotypes unique to PCV15 (serotypes 22F and 33F).…”
Section: Discussionsupporting
confidence: 82%
“…Antachopoulos et al reported a high incidence of complicated pneumonia caused by serotype 3, and a third of these patients had received complete PCV13 vaccination. A study carried out in Spain reported that serotype 3 was one of the most prevalent causes of parapneumonic empyema and was associated with a high rate of complications . A recent study made in Portugal by Silva‐Dacosta et al determine that the most fre­quent serotypes causing complicated pneumonia with PE or empyema between 2010 and 15 in children were 3, 1, and 19A, together accounting for 62% (68/109) of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated global vaccination coverage during the four years was 63.5% (48.2% in 2012, 63.9% in 2013, 68.5% in 2014, and 74.5% in 2015), according to the vaccination status of controls in a case‐control study conducted by our group during the same study period . In Table , there is a full spectrum of PCV coverage in cases with complicated pneumonia with Empyema and/or Pleural effusion, attending of no PCV, PCV7, PCV10, and PCV13.…”
Section: Methodsmentioning
confidence: 99%
“…Though the PCV-7 seems to be promising, but there have been reports of invasive pneumococcal disease due to the serotypes not covered by the PCV-7 65 . Advancement of vaccination strategy led to the introduction of PCV-13 vaccine, which contains thirteen different serotypes of the pneumococcal capsule, however the vaccine effectiveness of PCV-13 against serotype 3 (the same serotype used in my in vivo project, see table 12) remains questionable 66 . Overall, the emergence of antibiotic resistance and availability of principally useful, but still insufficient vaccines, results in high medical need for the generation of adjunctive therapies by better understanding of the pathogenesis of S. pneumoniae-induced inflammation…”
Section: Emergence Of Multi Drug Resistant (Mdr) S Pneumoniaementioning
confidence: 99%